2009
DOI: 10.1039/b905388c
|View full text |Cite
|
Sign up to set email alerts
|

Lipase dissolution and stabilization in ether-functionalized ionic liquids

Abstract: Ionic liquids (ILs) with various structures and properties have been extensively investigated in many biocatalytic reactions and processes. However, although hydrophobic ILs tend to stabilize the insoluble (suspended) enzymes, they usually have low hydrogen-bonding basicity with solutes, which limits the solubility of many substrates (such as D-glucose, ascorbic acid, and cellulose). In contrast, hydrophilic ILs (such as those based on chloride, acetate and dicyanamide) are able to dissolve many of these subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
104
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 88 publications
6
104
2
Order By: Relevance
“…In addition, these ether-functionalized ILs have relatively low viscosities (50-150 mPa s at 20°C) [35,41]. In this study, we intend to dissolve oils in these new ILs (Scheme 1), i.e., [Me(OEt) 3 (3).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, these ether-functionalized ILs have relatively low viscosities (50-150 mPa s at 20°C) [35,41]. In this study, we intend to dissolve oils in these new ILs (Scheme 1), i.e., [Me(OEt) 3 (3).…”
Section: Introductionmentioning
confidence: 98%
“…To seek ILs with higher substrate solubility and higher enzyme compatibility, we recently synthesized a series of new ether-functionalized ILs that are able to dissolve a variety of substrates (such as sugars, cellulose, ascorbic acid, and amino acids), but do not inactivate the lipase [35,41]. In addition, these ether-functionalized ILs have relatively low viscosities (50-150 mPa s at 20°C) [35,41].…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Therefore, the FT-ATR-IR spectra of enzyme and support (PS-DVD-CALB-1 and Novozyme 435) were recorded and analysed by deconvolution of the amide I region (Fig. 2b, Table 4).…”
mentioning
confidence: 99%
“…They reported that it was possible to achieve solubilities, at 35º C, of each carbohydrate up to 43.9, 49.0, 17.1 and 16.6 (g of carbohydrate per 100 g of IL), respectively [15]. Zhao et al found that ether-functionalized ILs can dissolve considerable amounts of D-glucose and cellulose [16], [17].…”
Section: Introductionmentioning
confidence: 99%